2016
DOI: 10.1155/2016/2918796
|View full text |Cite
|
Sign up to set email alerts
|

The Multifunctional Effects of Nobiletin and Its Metabolites In Vivo and In Vitro

Abstract: Nobiletin (NOB) chemically known as 5,6,7,8,3′,4′-hexamethoxyflavone is a dietary polymethoxylated flavonoid found in Citrus fruits. Recent evidences show that NOB is a multifunctional pharmaceutical agent. The various pharmacological activities of NOB include neuroprotection, cardiovascular protection, antimetabolic disorder, anticancer, anti-inflammation, and antioxidation. These events may be underpinned by modulation of signaling cascades, including PKA/ERK/MEK/CREB, NF-κB, MAPK, Ca2+/CaMKII, PI3K/Akt1/2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 93 publications
(101 reference statements)
3
84
0
1
Order By: Relevance
“…As shown in Figure 1b, NOB significantly reduced the viability of K562 cells in a time-and dose-dependent manner. The viability of cells treated with NOB (10,20,40,80, and 100 µM) for 24 h decreased to 92.4 ± 8.6%, 84.6 ± 9.9%, 75.6 ± 8.8%, 58.4 ± 6.1%, and 54.4 ± 5.3% of the control, respectively, while the viability of cells treated for 48 h decreased to 81.4 ± 3.5%, 69.1 ± 3.9%, 65.0 ± 6.1%, 51.3 ± 7.2%, and 46.2 ± 9.9% of the control, respectively (p < 0.01). The concentration to inhibit 50% of cell viability after 48 h treatment (IC 50 value) was 82.49 µM.…”
Section: Effects Of Nob On Cell Growth Of K562 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1b, NOB significantly reduced the viability of K562 cells in a time-and dose-dependent manner. The viability of cells treated with NOB (10,20,40,80, and 100 µM) for 24 h decreased to 92.4 ± 8.6%, 84.6 ± 9.9%, 75.6 ± 8.8%, 58.4 ± 6.1%, and 54.4 ± 5.3% of the control, respectively, while the viability of cells treated for 48 h decreased to 81.4 ± 3.5%, 69.1 ± 3.9%, 65.0 ± 6.1%, 51.3 ± 7.2%, and 46.2 ± 9.9% of the control, respectively (p < 0.01). The concentration to inhibit 50% of cell viability after 48 h treatment (IC 50 value) was 82.49 µM.…”
Section: Effects Of Nob On Cell Growth Of K562 Cellsmentioning
confidence: 99%
“…Nobiletin (5,6,7,8,3 ,4 -hexamethoxyflavone, NOB), a polymethoxyflavone (PMF), is present abundantly in the peels of certain citrus, such as sweet and mandarin oranges [16]. NOB has been demonstrated to possess a broad spectrum of bioactivities, including anti-inflammatory, anti-atherogenic, neuroprotective, and anti-tumor properties [17][18][19][20]. Moreover, the NOB shows inhibition of cell proliferation and invasion, arrest of cell cycle progression or induction of cell apoptosis in various types of solid tumors [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…16 Based on previous studies, nobiletin has been shown to have antitumor activity through antiproliferation mechanisms, apoptotic induction, cell cycle deregulation, 17 antiangiogenesis, 18 antiinflammatory and anticarcinogenic, 19 and other pharmacological activities through in vitro and in vivo assay. 20 As for the results of this study, Nobiletin has the potential to have anticancer activity through the mechanism of apoptosis involving the protein Bcl-xl in silico.…”
Section: Discussionmentioning
confidence: 66%
“…Nobiletin, chemically known as 5,6,7,8,3′,4′-hexamethoxyflavone, is a dietary flavone with the empirical formula C 21 H 22 O 8 and the molecular weight 402.39. It is found in the peel of various citrus fruits, such as oranges and tangerines [ 36 ]. Like other bioflavonoids, nobiletin has shown potential medicinal properties in several pathologies and their associated causes, such as preventing type 2 diabetes [ 37 ], protecting against bone mineral density loss [ 38 ], treating cancer [ 39 ], and lowering blood cholesterol [ 40 ].…”
Section: Main Citrus Flavonoids With Antidiabetic Effectsmentioning
confidence: 99%